2019
DOI: 10.3390/su11226202
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Information Fusion Methods for Gas Turbine Diagnostics

Abstract: The correct and early detection of incipient faults or severe degradation phenomena in gas turbine systems is essential for safe and cost-effective operations. A multitude of monitoring and diagnostic systems were developed and tested in the last few decades. The current computational capability of modern digital systems was exploited for both accurate physics-based methods and artificial intelligence or machine learning methods. However, progress is rather limited and none of the methods explored so far seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 82 publications
(103 reference statements)
0
15
0
Order By: Relevance
“…The fusion of information from different sources in order to address the limitations of different methods and enhance the capabilities of a decision support system has also been the focus of multiple research studies. It has been extensively used on the sensor level, but its use for decision support and diagnostics has been relatively limited (Zaccaria et al, 2019). However, since it offers benefits in dealing with incomplete data, it can be particularly beneficial for small and micro-scale gas turbines, allowing the development of an automated diagnostics and decision support system.…”
Section: Gas Turbine Monitoring For Maintenance and Diagnosticsmentioning
confidence: 99%
“…The fusion of information from different sources in order to address the limitations of different methods and enhance the capabilities of a decision support system has also been the focus of multiple research studies. It has been extensively used on the sensor level, but its use for decision support and diagnostics has been relatively limited (Zaccaria et al, 2019). However, since it offers benefits in dealing with incomplete data, it can be particularly beneficial for small and micro-scale gas turbines, allowing the development of an automated diagnostics and decision support system.…”
Section: Gas Turbine Monitoring For Maintenance and Diagnosticsmentioning
confidence: 99%
“…No less scientific papers [13][14][15][16][17][18] are devoted to parametric diagnostic methods. So, in [13] it was shown that information integration methods, such as Bayesian networks, fuzzy logic or probabilistic neural networks, can be used to implement a decision support system that can be used for parametric diagnostics of gas turbines. At the same time, the proposed decision support system does not contain information about the technical condition of the automatic control system of the gas pumping unit and does not allow using it to monitor the operability of the automatic control system.…”
Section: Literature Analysis and Problem Statementmentioning
confidence: 99%
“…Nevertheless, it has general applicability to other systems from varying domains, such as biomedical data analysis and any high risk technology generating sequential data or sensor data from arrays of sensor networks [22], [23]. A review of other information fusion methods for IGT diagnostics can be found in [24].…”
Section: Introductionmentioning
confidence: 99%